2017
DOI: 10.1016/j.anaerobe.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the source of microorganisms on adaptation of hydrolytic consortia dedicated to anaerobic digestion of maize silage

Abstract: The main aim of this study was to evaluate the effect of the source of microorganisms on the selection of hydrolytic consortia dedicated to anaerobic digestion of maize silage. The selection process was investigated based on the analysis of changes in the hydrolytic activity and the diversity of microbial communities derived from (i) a hydrolyzer of a commercial agricultural biogas plant, (ii) cattle slurry and (iii) raw sewage sludge, during a series of 10 passages. Following the selection process, the adapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
2
11
0
4
Order By: Relevance
“…However, their relative abundances in the digesters differed according to the operation temperature and digester compositions. As expected, Clostridiaceae and Ruminococcaceae whose members show high cellulolytic activity (Wang et al 2013;Poszytek et al 2017) were detected in all digesters (Fig. 5).…”
Section: Bacterial Community Pattern and Dynamicssupporting
confidence: 83%
“…However, their relative abundances in the digesters differed according to the operation temperature and digester compositions. As expected, Clostridiaceae and Ruminococcaceae whose members show high cellulolytic activity (Wang et al 2013;Poszytek et al 2017) were detected in all digesters (Fig. 5).…”
Section: Bacterial Community Pattern and Dynamicssupporting
confidence: 83%
“…In another study, a pure culture of Melioribacter roseus had a limited enhancing effect on methane yields of anaerobic reactors treating wheat straw under thermophilic conditions (53±1°C) representing an increase by 11%, whereas a pure culture of Clostridium thermocellum increased the methane yield by 34% [1]. Different from these pure culture studies, Poszytek and co-workers obtained hydrolytic enrichment cultures from different sources to enhance methane production in AD of maize silage [11]. In accordance with our results, they showed that the level of enhancement depended on the original inocula and that a 10% (v/v) addition of bioaugmentation cultures increased the biogas production by 10-29%.…”
Section: Bioaugmentation Potential Of Different Enrichment Cultures Imentioning
confidence: 99%
“…Schmidt et al [14] used bioaugmentation during the anaerobic digestion of sewage sludge to improve the polycyclic aromatic hydrocarbons removal. Moreover, the bioaugmentation of anaerobic digestion communities by the adapted hydrolytic consortia increased the biogas yield by 10–29% in the anaerobic digestion of maize silage [15]. …”
Section: Introductionmentioning
confidence: 99%